Geospatial applications for natural resources management - Singh, Chander Kumar; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This book will present new research regarding the interdisciplinary applications of spatial information sciences for identification, assessment, monitoring, and modeling issues related to natural resources and environmental management. It will focus on the creation, collection, storage, processing, modeling, interpretation, display and dissemination of spatio-temporal data, which could greatly aid with environmental management issues including ecosystem change, resource utilization, land use management, and environmental pollution. The positive environmental impacts of information technology advancements with regard to global environmental and climate change will also be discussed.
chapter 1 Spatiotemporal Analysis of Urban Expansion and Its Impact on Surface Temperature and Water Bodies / Chander Kumar Singh -- chapter 2 Landscape Pattern and Dynamics in a Fast-Growing City, Khamis-Mushyet, Saudi Arabia, Using Geoinformation Technology / Javed Mallick -- chapter 3 Understanding the Spatio-Temporal Monitoring of Glaciers -- Application of Geospatial Technology / Shruti Dutta -- chapter 4 Urban Imprints on City$1 (Bs Environment$1 (BUnfolding Four Metro Cities of India /s Richa Sharma -- chapter 5 Predictive Modeling of a Metropolitan City in India Using a Land Change Modeling Approach / Akanksha Balha -- chapter 6 Performance Analysis of Different Predictive Algorithms for the Land Features Modeling / Pradeep Kumar -- chapter 7 Urban Growth and Management in Lucknow City, the Capital of Uttar Pradesh / Akanksha Balha -- r
Keywords: Ecology; Environmental management; Natural disasters; Natural resources -- Management; Remote sensing; SCIENCE -- Earth Sciences -- Geography; TRAVEL -- Budget; TRAVEL -- Hikes & Walks; TRAVEL -- Museums, Tours, Points of Interest; TRAVEL -- Parks & Campgrounds; TECHNOLOGY & ENGINEERING / Environmental / General; TECHNOLOGY & ENGINEERING / Remote Sensing & Geographic Information Systems; Climate Dynamics; Fluvial Dynamics; Forest Conservation; Glacier Monitoring, Snow Melt, Runoff Modeling; Land Use; Water Resources; Environmental management -- Geographic information systems; Natural resources -- Management -- Geographic information systems